Heavy metal fractionation in Fluvic Entisols under saline conditions in Northeastern Brazil - Eugenia Ortiz Escobar, Maria; Rocha da Silva, Esdras; Senna de Oliveira, Teogenes; Felipe Ferreyra Hernandez, Fernando (Revista Ciência Agronômica, 2023)
The long-term use of agrichemicals might add some heavy metals to soils and, there is little information about thedynamics of these elements in soils under saline conditions in semiarid regions. This study aimed to investigate the dynamics of heavymetals in the diff erent fractions of Fluvic Entisols with saline conditions under long term of coconut cultivation in a semiarid region.Composite soil samples were collected in fi ve agricultural areas and three areas under native vegetation. Physical, chemical, and heavymetal analyses were carried out in soil (semi total and fractionated contents). Quality of irrigation water and drainage water was alsoevaluated. Analytical results were normalized and subjected to analysis of variance, and means were compared by Scott-Knott test (P < 0.05).Pearson correlation analysis was also used to assure a minimum correlation of variables justifying its use in the matrix of a factorialanalysis. Semi-total contents of Cr, Ni, Pb and Zn (except Cu in some areas) were lower than previous local assessment and nationalguiding values, indicating that they do not cause harmful alterations in soil quality. Analyses of waters showed high levels of HCO3,indicating moderate restriction to use (due to the high levels of EC, SAR, Na and Cl). Fractionation of heavy metals revealed low risk ofenvironmental pollution since most metal contents were bound to the oxidic, organic and residual fractions. The water used in irrigationcontributes to the contents of heavy metals and to the salinity condition of the evaluated soils.